MENA Quarterly Economic Brief, July 2014 : Predictions, Perceptions and Economic Reality - Devarajan, Shanta; Mottaghi, Lili (Washington, DC: World Bank, 2014)
This issue of the MENA quarterly brief assesses the macroeconomic performance of seven of the MENA countries: Egypt, Tunisia, Iran, Lebanon, Jordan, Yemen and Libya. All of these countries experienced rapid economic growth during 2000-10, and suffered a sharp economic slowdown in the aftermath of 2011. The brief focuses on the challenges facing these countries with a closer look at the actual growth performance in comparison with their forecasts and highlights the limitations of forecasting in the wake of the 2011 uprisings; and at the consequences of the growth slowdown, including unemployment, where perceptions may diverge from reality. The story is told in fourteen charts.